Implementation of electronic government procurement (e-GP) in Bangladesh Bureau of Statistics (BBS) : impact on present procurement practices and future scopes - Hossain, Md. Arif (Brac University, 2024)
A thesis submitted to the Brac Institute of Governance and Development in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management,2024.